# Yahoo Web Search

1. Sort by

1. ### Is 709-677 equal to 32 or 29 or 229? Very confused with this problem..?

... 0 - 7 ??? Can't do!!! So 'borrow' 10/1 from the LHS This becomes 10 - 7 = 3 LHS Under the '...

1 Answers · Education & Reference · 03/05/2016

2. ### Calculus Help!!?

...which a gives a perfect cube? We note a=3 gives 16/2 = 8 = LHS , OK! The tangent point T = (3, 4) => the distance d = √(3-19...

1 Answers · Science & Mathematics · 29/04/2015

3. ### I need help with a physics question:?

... to GT² / 4π² = r³ / M and since the LHS is the same for Earth and Mars, r³ / 0.5M...

1 Answers · Science & Mathematics · 11/04/2015

4. ### Physics Manometer Question?

On the LHS, P1 = Patm + rho*g*H. where rho is the density of water...

1 Answers · Science & Mathematics · 14/05/2015

5. ### Prove each of the following. Use proper LHS/ RHS format for full marks. 1. cosθcotθ= 1/sinθ -sinθ 2. 1+cotθ/ cscθ = sinθ+ cosθ?

Here's the first as an example of the layout: LHS = cosθcotθ = cosθ * cosθ/sinθ ... because cotθ = 1/tanθ = cos^2θ / sinθ = (1 - sin...

1 Answers · Science & Mathematics · 28/01/2015

6. ### Solving Differential Equations?

e^(y) * dy/dx = (4x + 4) / (9cos(y) - sin(y)) e^(y) * (9cos(y) - sin(y)) * dy = 4 * (x + 1) * dx 9 * cos(y) - sin(y) => sqrt(9^2 + (1)^2) * ((9/sqrt(82)) * cos(y) - sin(y) * (1/sqrt(82))) => sqrt(82) * ((9/sqrt(82)) * cos(y) - (1/sqrt(82)) * sin(y)) sin(t) = 9/sqrt(82) cos(t) = 1/sqrt(82) sqrt(82) * (sin(t)cos(y) - sin(y)cos(t)) => sqrt(82) * sin(t - y) => -sqrt(82...

2 Answers · Science & Mathematics · 19/01/2015

7. ### Rationals and Radicals. 1) Solve for k:E=1-c/k 2)Simplify.(Rationalize the denominator if necessary) a.sqrt5/3x^2 b.4sqrtb/sqrt3-b?

... k from both sides: Ek – k = -c Factoring the LHS: k(E – 1) = -c k = -c / (E – 1) 2) (a) (√5) / (3x²) can...

2 Answers · Science & Mathematics · 16/01/2015

8. ### Fibonacci Induction Problems?

...1: prove validity of theorem for start value(s) of n n = 1: LHS: fn = f1 = 1 RHS: r^(n-2) = r^(1-2) = r^(-1) = 1...recursive definition of fibonacci sequence ... = f[2k+1] - 1 ==> LHS = RHS, hence the theorem is true for n = k+1...

1 Answers · Science & Mathematics · 25/11/2014

9. ### Trig Identity?

sin(A+/B) = (sinAcosB +/- cosAsinB) so, LHS: sin(A+B)sin(A--B) = (sinAcosB+cosAsinB...

1 Answers · Science & Mathematics · 11/11/2014

10. ### Implicit differentiation question? Hey can any one tell me how to do these questions. I still don't understand implicit differentiation.?

...27 - 5(x^2)*y) d(y^3) - d(10xy) = d(- 5(x^2)*y) ... for the second term in LHS we need the Product Rule; also for the RHS ... 3*(y^2)*dy...

1 Answers · Science & Mathematics · 15/10/2014